2000
DOI: 10.1002/(sici)1097-4652(200007)184:1<70::aid-jcp7>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Generation of active TGF-? by prostatic cell cocultures using novel basal and luminal prostatic epithelial cell lines

Abstract: Two prostatic epithelial lines, one of basal origin and one of luminal origin, were established from the dorsolateral prostates of p53 null mice. The cell lines are nontumorigenic when inoculated subcutaneously under the renal capsule or intraprostatically in syngeneic mice. The luminal cell line (PE-L-1) expresses cytokeratins 8 and 18 and the basal cell line (PE-B-1) expresses cytokeratins 5 and 14. The basal cells require serum for growth, whereas the luminal cells grow only in serum-free medium. Both cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 75 publications
1
44
0
Order By: Relevance
“…To quantitatively measure Trop2 localization, a mouse prostate epithelial basal (PEB) cell line (Salm et al 2000) that expresses endogenous Trop2 was used. PEB cells were infected with lentivirus expressing RFP or RFP and Trop2 modified with a C-terminal Myc tag to follow Trop2 ICD.…”
Section: Resultsmentioning
confidence: 99%
“…To quantitatively measure Trop2 localization, a mouse prostate epithelial basal (PEB) cell line (Salm et al 2000) that expresses endogenous Trop2 was used. PEB cells were infected with lentivirus expressing RFP or RFP and Trop2 modified with a C-terminal Myc tag to follow Trop2 ICD.…”
Section: Resultsmentioning
confidence: 99%
“…Paradoxically, it also promotes the expression of prometastatic genes and the development of bone metastases (44). TGFb is also important in the normal prostate, where cellular interactions between luminal epithelial cells and stromal cells determine the amount of active TGFb, in order to maintain tissue homeostasis (45). It is our assertion that CD73 expression in normal prostatic epithelium may also be regulated by TGFb.…”
Section: Discussionmentioning
confidence: 95%
“…To the best of our knowledge, this is the ®rst direct demonstration of an increased secretion of TGFb2 by epithelial cells, under the control of a diffusible factor secreted by ®broblasts. In a recent study, the authors demonstrated that co-culture of mice prostate epithelial cell line with smooth muscle cells increases TGFb secretion, but were not able to determine which cell type was the source of this secretion [35]. Other authors have studied the effect of co-culture of prostate epithelial cells and stroma, on epithelial cell growth.…”
Section: Discussionmentioning
confidence: 99%